PHYTOCHEMICAL AND FT-IR SPECTROSCOPIC ANALYSIS OF THE ROOT BARK OF SARCOCEPHALUS LATIFOLIUS (SMITH BRUCE) - Isah, Y.; Alfa, C. (FUDMA JOURNAL OF SCIENCES, 2023)
This research work was aimed at quantitative phytochemical screening and bioactive functional groups analysis of the crude extracts of the root bark of Sarcocephalus Latifolius (Smith Bruce) present. The phytochemical screening revealed the presence of carbohydrate, glycoside, tannin, saponins, resin, flavonoid, alkaloid, triterpenoid, anthraquinone, and terpenoid, and the absence of steroid and phlobatannins for all the extracts. The quantitative analysis gave 5.25% of alkaloid, 15.69% of flavonoid, 10.2% of saponins and 2.05 of tannin. The FT-IR analysis showed major peaks at 2854.74 cm-1 (alkanes), 1656.84 – 1651.12 cm-1 (alkenes), 1589.4 – 1450.52 cm-1 (aromatic ring), 3417.98 – 3394.84 cm-1 (phenols and alcohol), 2924.18 – 2723.58 cm-1 (carboxylic acid, O-H stretch), 1735.99 – 1651.12 cm-1 (ketone, C=O stretch), 2731.29 – 1697.41 cm-1 (aldehyde, C-H Stretch), 1041.6 – 1033.88 cm-1 (Ester, C-O Stretch), 1226.77 – 1172.76 cm-1 (Ethers, C-O Stretch) and 3417.98 – 3394.83 cm-1 (N-H bend). The presence of these prominent functional group may be responsible for the extracts bioactivity and may equally account for the varied ethno medicinal uses of the plant in folk medicine.